Quantitative genetic analysis of respiratory function and related traits in Bulldogs, French Bulldogs and Pugs - Joanna Jadwiga Ilska; Fern McDonnell; Jane Frances Ladlow (PLoS ONE, 2026)
Brachycephalic Obstructive Airway Syndrome (BOAS) is a common health issue in brachycephalic breeds like Bulldogs, French Bulldogs, and Pugs, linked to their distinctive skull morphology. Despite its prevalence, the genetic basis of respiratory dysfunction in these breeds remains poorly characterised. To enable selection against BOAS, the Respiratory Function Grading Scheme (RFGS) was established in 2019, where respiratory function of dogs considered for breeding is tested via a standardised exercise test. Here, we analysed RFGS data from over 4,000 dogs, alongside pedigree records, to estimate heritability of respiratory function and assess RFGS participation across the UK Royal Kennel Club registered populations of the three extreme brachycephalic breeds. Moderate heritability estimates for RFGS grade (0.21–0.49), and nostril stenosis (0.31–0.39), with significant genetic correlations between the traits indicate that within-breed selective breeding can improve respiratory health. These findings support the feasibility of breeding programs targeting respiratory function. Implementing such strategies, alongside increased health screening participation, may help mitigate BOAS prevalence and enhance welfare in these popular breeds.